Optimalisasi Peran Mahasiswa KKN dalam Penguatan Pembelajaran Al-Qur’an di Lingkungan Rumah Qur’an Kelurahan Tangkahan - Sakinah, Nur; Naimi, Nadlrah (EL-EMIR INSTITUTE, 2025)
The Community Service Program (KKN) is a form of student engagement with society that aims to provide tangible contributions in accordance with their academic expertise. This study aims to describe the optimization of KKN students’ roles in strengthening Qur’anic learning at the Rumah Qur’an in Tangkahan Sub-district. A qualitative descriptive approach was employed, with data collected through observation, interviews, and documentation of activities. The findings reveal that KKN students play a strategic role in enhancing the community’s motivation to learn the Qur’an, both among children and adults, through activities such as teaching Qur’anic reading, assisting in tajwid and tahsin, as well as organizing educational competitions that foster enthusiasm for learning. Furthermore, students contribute by introducing more engaging and practical learning methods. The community perceived significant impacts, including increased interest, participation, and comprehension in proper Qur’anic recitation based on tajwid principles. Thus, the presence of KKN students has been proven to optimize the function of the Rumah Qur’an as a non-formal educational center in fostering a Qur’anic generation in Tangkahan